Philosophical Culture of Laughter and the Psychology of Humor - Vasilyevna Artemyeva, Tatiana (2017)
The study of the phenomenon of laughter opens up opportunities in understanding the phenomenon of culture, since humor is an important element of culture, reflects the characteristics of national consciousness and attitude, is a means of regulating and preserving social values. The phenomenon of humor in Russian psychology is not fully disclosed, so it is important to turn to philosophy, cultural studies, in terms of which several areas of the study of the comic are of interest for psychology: the comic as deviation from the norm and the destruction of the sign system; distinguishingphysiological laughter and social (cultural)laughter; the proportion of emotions and intellect in the comic.The analysis makes it possible to assert that the phenomenon of the comic is essential to study in all its manifestations in wholeness and unity: the physiological laughter and the comic laughter, the unity of emotion and intellect in understanding and creating the comic. It has been revealed that humor possesses a powerful potential, allowing the individual not to easily accept the norms and laws of society, but show some flexibility in the interpretation of these norms.